Protective Effect of Glycine and Tri-Methyl Glycine (Betaine) Against Heavy Metals-Induced Oxidative Stress in Liver-Derived Post-Nuclear Supernatant (PNS) - Reza Heidari; Hamidreza Mohammadi; Asrin Ahmadi; Vahid Ghanbarinejad; Faraz Kasra; Amir Khosravi (Shiraz University of Medical Sciences, 2018)
Heavy metals are environmental pollutants which pose toxicity toward biological systems. Most organs are susceptible to heavy metals-induced toxicity. Hence, finding protective agents against heavy metals-induced toxicity is valuable. The post-nuclear supernatant (PNS) has been accepted as an in vitro model for assessing xenobiotic-induced toxicity toward biological systems. Monitoring the toxic effects of a large number of xenobiotics in a short time is one of the superiorities of PNS system. The goal of the present study was to validate the PNS as an in vitro model for investigating the effect of heavy metals (Cd, Co, Cu, Fe, As, Hg, Cr, and Pb)-induced toxicity and evaluating the potential protective effects of glycine and betaine. Markers of oxidative stress including ROS formation, lipid peroxidation and glutathione content in addition of succinate dehydrogenase activity (MTT test) were monitored in the presence of heavy metals alone or in combination with glycine (1 mM) and betaine (100 µM). Our results suggest that PNS preparations can be used as an appropriate model for future investigation of xenobiotics-induced toxicity and estimation of the protective properties of different agents. Indeed, further evaluations in other experimental models could reveal the protective properties of betaine and glycine against heavy metals-induced organ injury.